An Analytical Study of the Organizational Reputation of the Women’s Committee in the Iraqi Football Association - Ali, shahad; Kareem , Nibal (Journal of Physical Education, 2025)
The study is interested in examining the organizational reputation of the Women’s Committee at the Iraqi Football Association. Description of Work The descriptive design was conducted on a community sample of 218 Iraqi Football Association population. The researchers utilized a questionnaire as a data collection instrument and included 5 domains including leadership, creativity culture and structure; public relations capability, quality of performance and governance in their instrument. The findings demonstrated an acceptable level of institutional image for the women’s committee altogether (firms and organizations) which would suggest that constructive measures have been taken regarding performance enhancement and promotion of sports in Iraq. The key recommendations focused on improving the transparency and trust in decision making and crisis management processes, assisting with developing capacities of personnel working for the women’s committee through professional training programmers, and increasing support to local projects encouraging girls’ participation in sports.